Paul and the salvation of the individual - Burnett, Gary W. (Biblical interpretation series, 2001)
This work suggests that it is possible to maintain that Paul had a lively interest in the salvation of the individual, without having to revert to traditional Lutheran interpretations of the text. It focuses on three important texts in Romans.